ENGEMBANGAN KAPASITAS PEMERINTAH: STUDI DI PERPUSTAKAAN UMUM DAERAH â€œRUMAH BACA HAFRITA DARAâ€ KABUPATEN SIAK TAHUN 2015-2016 - Ariska, Rina; ", Erman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research was motivated by the importance of the role and library function in serving the needs of the community. In accordance with the primary objective mandated by UUD 1945, namely the intellectual life of the nation. To that end, the library can not walk alone without support from various parties, both public and local government. Hence the need for capacity building of government in the management of public libraries, simply capacity is the basis of regional autonomy, because the capacity is the basis for independence. Enhancing the performance of the government in conducting a business in the field of librariesand archives have made the district siak to meet one of he standards of national libraries, the public library in â€œhouse read Hafrita Daraâ€ siak has managed to become a library level of regency,cityâ€™s first and only wan in Riau Province that has been accredited A.The purpose of research is to find out and analyze the policy of library office and archives siak in the development of the management capacity of the public library in â€œhouse read Hafrita Daraâ€ Siak, research method is qualitative descriptive research data collection is done by observation, interviews, and documentation.Results of this study is researchers know whwn accredited library siak have nolegallibrary management and still refers to the central policy. Capacity development policy office district libraries and archives siak years 2015-2016 conducted through the program referrig to the increased interest in reading peopleand culture district siak through: improvement of libraries services, improving quality of human resources of the library, dissemination and publication, improved financial management. Implementation of the programand the policy is influenced by: leadership, commitment, institutional reform,and regulatory reform. In this study, researchers concluded that the limitations of local government through the office of the library and archives of siak continue to maximize the resources available to achieve the vision and mission of the district development siak particularly in the field of library and archive with the same commitment of foster and institutional reform.Keyword : Capacity Building, Local Government, Public Libraries